The modus operandi between hire purchase and hire purchase – I (Al – Ijarah Thumma Al – Bai) in Maybank Malaysia / Nazirah Mohamad Aziz - Mohamad Aziz, Nazirah (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Hire purchase and hire purchase – I (AITAB) in Maybank Malaysia generally is financing for a new vehicle, second hand and reconditioned motor vehicle. The modus operandi of hire purchase and AITAB when the car will be held by the bank first and after the fully payment the customer will get the vehicle after the end of the payment. There are differences between hire purchase and hire purchase – I. The hire purchase and hire purchase - I (AITAB) definitely are subject to Hire Purchase Act 1967. The interest rate for the conventional bank in vehicle financing can be consider as floating rate and fixed rate. For the Islamic bank there is no interest rate but as compensative charges. Furthermore, AITAB is Shariah compliant product because no other additional charges such as interest rate that lead to prohibited contract. The interviewer that involve information being integrated on related topics. This study focused on the modus operandi of hire purchase and hire purchase – I (AITAB) to be conducted in Maybank Malaysia. Consequently, the findings and its modus operandi were discussed.